CAREGIVERS' NEEDS IN CARING FOR RELATIVES WITH SCHIZOPHRENIA IN MEDAN INDONESIA: A PHENOMENOLOGICAL STUDY - Jenny Marlindawani Purba (Belitung Raya Foundation, 2017)
Background: A caregiver is a primary nurse and has a major role in providing care for people with schizophrenia. Caring for those with schizophrenia for a long period of time is a challenge for families, especially caregivers. Various needs ought to be studied by nurses to assist caregivers in providing optimal care for family members who experience schizophrenia. Objective: This qualitative study aims to explore the needs of caregivers in treating schizophrenia at home. Methods: The method used in this study is the method of purposive sampling with the number of participants as many as 10 people with criteria: 1) have family members diagnosed with schizophrenia, 2) directly involved in home care patients, 3) caring for schizophrenia for more than one year, 4) willing to be a participant by signing informed consent, 4) being able to identify what is needed in treating schizophrenia. Colaizzi is used to analyze interview data. Results: The results of the study found four themes of caregiver needs in caring for schizophrenia patients at home, namely: 1) seeking information about schizophrenia, 2) sought schizophrenic relatives' recovery, 3) looking for appropriate rehabilitation for relatives with schizophrenias, and 4) utilizing mental health facilities. Conclusions: It is expected that nurses have the knowledge and skills in identifying and helping families, especially caregivers, to meet unmet needs so they can optimize home care.